Richer (and Holier) Than Thou? The Effect of Relative Income Improvements on Demand for Redistribution - Mounir Karadja; Johanna Möllerström; David Seim (Research Institute of Industrial Economics (IFN), 2014)
We study the extent to which people are misinformed about their relative position in the income distribution and the effects on preferences for redistribution of correcting faulty beliefs. We implement a tailor-made survey in Sweden and document that a vast majority of Swedes believe that they are poorer, relative to others, than they actually are. This is true across groups, but younger, poorer, less cognitively able and less educated individuals have perceptions that are further from reality. Using a second survey, we conduct an experiment by randomly informing a subsample about their true relative income position. Respondents who learn that they are richer than they thought demand less redistribution and increase their support for the Conservative party. This result is entirely driven by prior right-of-center political preferences and not by altruism or moral values about redistribution. Moreover, the effect can be reconciled by people with political preferences to the right-of-center being more likely to view taxes as distortive and to believe that it is personal effort rather than luck that is most influential for individual economic success.
Keywords: D72; H23; 330; Redistribution; Political preferences; Inequality